An investigation of Fair Trade product knowledge, beliefs, experiences and buying intentions of Generation Z in the US. (30th March 2022) - Pavlovskaia, Zoia; Kara, Ali
Abstract : The Fair Trade movement is an alternative way to conduct international and domestic business by trying to improve trading conditions of disadvantaged producers around the world through consumer actions. Consumers can support the movement by purchasing FT certified products, which confirm that products meet ethical principles and environmental standards that are set in accordance with the requirements. However, FT product sales in the US have been lagging in comparison to the FT product sales in Europe. For instance, per capita consumption of the value of FT products was approximately €3 in the US in comparison to €34 in the UK (Fairtrade International, 2016). This study investigates several variables that can influence Fair Trade consumption, and, specifically, the effects of consumers' knowledge, beliefs and past experiences on their purchase intentions of Fair Trade products among urban youth consumers in the US. Using the Theory of Reasoned Action as the conceptual framework, data were collected from 154 subjects using an online survey. The results indicate that consumer knowledge about FT has significant positive influence on their purchase intentions, but this relationship is mediated and strengthened by their beliefs and past behaviour. We offer various implications of these findings to FT businesses and organisations.